PERAN AKTOR DALAM PENGEMBANGAN OBJEK WISATA GOA KREO DI KOTA SEMARANG - Salsabela, Rahmania Rifka; Santoso, R. Slamet; Subowo, Ari (Journal of Public Policy and Management Review, 2024)
Semarang City has become a destination for tourist both domestically and internationally. The establishment of tourist attractions aims to empower the community, encouraging active participation to raise araeness of the tourism potential at each of these attractions. However, the development of the tourist attraction, Goa Kreo, has not yet reached its development. In this research, the researcher utilizes a descriptive qualitative research method. The actor involed in the development of Goa Kreo include the Department of Culture and Tourism (Disbudpar) of Semarang City, the Regional Development Planning Agency (Bappeda) of Semarang City, the Regional Technical Implementation Unit (UPTD) of Goa Kreo, the Department of Planning and Development (DPU) of Semarang City, Kandri Sub – district, Sukomakmur Tourism Awareness Group (Pokdarwis), the local community of Kandri, and tourists visiting Goa Kreo. The conclusion of this research is that there is still suboptimal collaboration among actor hindering the development of Goa Kreo. Therefore, the researcher recommends improving the relationships among actor and enhancing communication to ensure the efficient development of Goa Kreo as a tourist attraction.